To do this, you need to solve either one of the equations for y or x. I'm going to solve for y in the first equation:
6x + 3y = 9
Subtract 6x from both sides:
3y = 9 - 6x
Divide both sides by 3:
y = 3 - 2x
Now that you know what y is equal to, you can substitute it into the second equation:
2x + 3y = 1
2x + 3(3-2x) = 1
Distribute the 3:
2x + 9 - 6x = 1
Combine like terms:
9 - 4x = 1
Subtract 9 from both sides:
-4x = -8
Divide by -4:
x = 2
No substitute this 2 into either one of the equations to get y. I'm going to use the first:
6x + 3y = 9
6(2) + 3y = 9
12 + 3y = 9
Subtract the 12 from both sides:
3y = -3
Divide by 3:
y = -1
ANSWER:
x = 2
y = -1
You can always check by substituting the values into the equations.
Read more on Brainly.com - brainly.com/question/3461332#readmore